2007
DOI: 10.1007/s00192-007-0515-5
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan treatment of interstitial cystitis/painful bladder syndrome

Abstract: The aim of this study is to evaluate the efficacy of intravesical hyaluronan therapy in interstitial cystitis/painful bladder syndrome (IC/PBS). One hundred twenty-six patients with IC/PBS and an average disease duration of 6.1 years were treated with weekly instillations of a 50-cm3 phosphate-buffered saline solution containing 40 mg sodium hyaluronate. To be eligible for hyaluronan treatment, a positive modified potassium test was requested as a sign of a urine-tissue barrier disorder. Data were obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
5

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(79 citation statements)
references
References 29 publications
5
64
0
5
Order By: Relevance
“…The largest ES in all CT studies was observed for HMW-HA in the study by Shao et al (Fig. 2) [34], with similar findings in two UCT studies with HMW-HA [16,40] by a superior Bd^for average VAS difference. Closest to this VAS reduction were the results obtained using 300 mg of intravesical PPS [47].…”
Section: Evaluation Of Efficacysupporting
confidence: 74%
See 2 more Smart Citations
“…The largest ES in all CT studies was observed for HMW-HA in the study by Shao et al (Fig. 2) [34], with similar findings in two UCT studies with HMW-HA [16,40] by a superior Bd^for average VAS difference. Closest to this VAS reduction were the results obtained using 300 mg of intravesical PPS [47].…”
Section: Evaluation Of Efficacysupporting
confidence: 74%
“…By far the largest effect sizes (d>2) for symptom reduction were found in 3 studies performed with HMW-HA [16,34,40].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The most accepted theory is the disruption of bladder lining glycosaminoglycan (GAG) layer [18]. There are many treatment modalities, although there is no cure [19]. The current treatment modalities give only a relief of symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…12 HA is widely studied and has shown a wide range of symptom improvement, from 30% to 85%. 3,13,14 Recently, Engelhardt and colleagues reported their long-term results of intravesical HA therapy and they observed a 50% complete bladder symptom remission at the 5-year follow-up without any additional therapy, while 41.7% with symptom recurrence improved with HA maintenance therapy. 15 On the other hand, in a double-blind, placebo-controlled, multicentre clinical study of different hyaluronic acid preparations (40 or 200 mg/cc), no significant efficacy of sodium hyaluronate compared to placebo was found for IC patients; however, further details, including patient selection, inclusion/exclusion criteria, definition of improvement/success, are not available.…”
Section: Discussionmentioning
confidence: 99%